Recepcja twórczości filmowej Grigorija Czuchraja w Polsce - Kalita, Liliana (Acta Polono-Ruthenica, 2018)
The text aims at presenting the discussion and evaluation of Grigorij Czuchraj’s films, the creator of the new wave in the Soviet cinema, as conducted by Polish film critics. The artist’s films have received numerous reviews and comments both in specialist and popular press, as well as on the Internet. The younger generation have been able to get acquainted with Czuchraj’s films thanks to the DVD collection. The criticism points out the importance of the director in Polish-Russian cultural relationships, and describes the way his works have been perceived by Polish viewers.